Optimalisasi Pengelolaan APBDes dalam Peningkatan Pembangunan Infrastruktur di Desa Bungurasih - Dhiva Anjar Kusuma Fajrin; Fitri Novitasari; Marcella Mardiana; Pratiwi Indah Maharani; Najwa Aulia Putri Ditia (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
Village infrastructure is an important foundation for local economic development and improving the welfare of the community in the area. However, the obstacles often encountered include ineffective budget planning, lack of community participation, and weak supervision in budget implementation. Nevertheless, there is potential for improvement through the implementation of an integrated village financial information system and active community involvement in the village development planning deliberation process (Musrenbangdes). This study employs a qualitative approach, utilizing primary data obtained through interviews and secondary data from journal sources and previous research. The results of this study indicate that village infrastructure development through the APBDes begins with the participatory preparation of the RKP, involving RT, RW, and BPD. Funding comes from the APBDes, PAD, and community self-help. The focus of development has now shifted to community empowerment, especially women, through skills training. APBDes management faces challenges in meeting sudden needs and relies on deliberation for solutions. Transparency is maintained through budget publication, and project implementation considers environmental aspects. Evaluations are conducted by the Inspectorate and District Office, while the community also monitors and critiques implementation. Regarding the food security program, there will be a shift in management to BUMDes starting in 2025, pending new regulations. The APBDes covers revenue, expenditures, and financing, with village deliberations as the highest forum for approval. Village funds are considered insufficient, so assistance from the Regional People's Representative Council (DPRD) also plays an important role.